A Scholarship Award Recommendation System by Integrating Interpolation and Profile Matching Methods - I Made Pande Darma Yuda; I Made Agus Wirawan; Putu Hendra Suputra (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2026)
Scholarships are financial aid provided to students to support the continuity of their studies. Universitas Pendidikan Nasional (UNDIKNAS) offers various scholarship programs, both from internal sources and external institutions, with limited quotas. However, the selection process, which has not been fully based on objective assessment, has resulted in outcomes that do not optimally reflect the actual eligibility conditions of applicants. To determine appropriate scholarship recipients, a selection mechanism based on objective and representative criteria is required. This study identifies 15 criteria derived from four types of scholarships, namely Kartu Indonesia Pintar (KIP) Kuliah, PPA, Unggulan, and Bank Indonesia, including parental income, parental education, number of dependents, residential status, land area, building area, electricity capacity, average report card score, academic and non-academic achievements, type of vehicle, foreign language proficiency, and certificate of financial hardship. Furthermore, the weighting of these criteria is conducted using the Entropy method to objectively determine the level of importance of each criterion. The Decision Support System (DSS) is designed by applying a two-point linear interpolation method to determine the alternative values for each criterion, while the Profile Matching method is used to match the participants’ profiles with the ideal profile, calculated based on core factor and secondary factor weights. This study utilizes 82 Undiknas scholarship data from the 2021 to 2024 cohorts and 44 Bank Indonesia scholarship data from the 2022 and 2023 cohorts. The results of this study indicate that the Interpolation method is capable of generating alternative values for each criterion in an objective and structured manner, as the calculations are based on a mathematical approach that considers predefined value ranges. Based on the evaluation and testing conducted, one weight combination demonstrated a high level of ranking consistency between the actual ranking results and the predicted rankings, namely the 0.50:0.50 weight combination with a value of 0.84168653. This value is categorized as very strong, as it falls within the range of 0.80–1.00 according to the predetermined Spearman Rank correlation interpretation scale.